2011
DOI: 10.15282/jmes.1.2011.7.0007
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Studies in the Static Components of A Centrifugal Compressor Stage

Abstract: Aerodynamic studies in the static components of a centrifugal compressor stage were conducted using the computational fluid dynamics solver FLUENT. For the simulation study, a typical centrifugal compressor stage geometry with a flow coefficient of 0.053 was chosen, The study is confined to the static components of the centrifugal compressor stage, i.e., the crossover bend (180° U-bend), a radial cascade of return channel vanes, and the exit ducting (90° L-turn). The aerodynamic performance is reported in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Turbulence effects are evaluated using the standard k-ε turbulence model because several studies have indicated the suitability of this model for the simulation of centrifugal compressors. [34][35][36][37][38][39][40] The numerical results of the current study also verifies this finding.…”
Section: Governing Equations Computational Domain and Boundary Condit...supporting
confidence: 82%
See 1 more Smart Citation
“…Turbulence effects are evaluated using the standard k-ε turbulence model because several studies have indicated the suitability of this model for the simulation of centrifugal compressors. [34][35][36][37][38][39][40] The numerical results of the current study also verifies this finding.…”
Section: Governing Equations Computational Domain and Boundary Condit...supporting
confidence: 82%
“…Similarly, Reddy et al 24,25 compared the flow characteristics for three different models of the return system, in terms of the inlet blade angle, blade chord and blade thickness for a centrifugal compressor stage with the flow coefficient of 0.053 at the design and off-design points. The numerical results illustrated that increasing the negative incidence on the leading edge of the vaned return channel causes fluid acceleration up to 30% chord length from the leading edge on the suction side.…”
Section: Introductionmentioning
confidence: 99%